VD_FINDINFO Arrêt / 2010 / 1097 vom 11. Juni 2010 - VD Tribunal cantonal (2010)
RETRAIT DE L'AUTORITÉ PARENTALE, INTERNATIONAL, RÉSIDENCE HABITUELLE | 311 al. 1 ch. 1 CC, 311 al. 1 ch. 2 CC, 315 al. 2 CC, 399a CPC